Kompleks Besi(II) Dengan Ligan 3-BPP : Review - Fitriani Fitriani; Djulia Onggo; Irma Mulyani (Jurnal Kartika Kimia, 2021)
The change of two different spin electronic states under the influence of temperature, pressure and light irradiation is known as the Spin Transition or Spin Crossover (SCO) phenomenon. Spin transition exists on octahedral complexes with an intermediate ligand field, one of the ligands is 2,6-bis (pyrazol-3-yl)pyridine or 3-bpp. Spin transition complexes were intensively investigated because they are highly potential candidates for electronic materials, such as sensors, molecular switches and information storages. The iron(II) complex with 3-bpp ligand has shown SCO characteristics including different transition pattern and transition temperature which were influenced by type of the counter anions. The iron(II) complexes with different types of counter anions have exhibited SCO phenomenon, due to the effect of temperature with abrupt transition. However, the presence of hydrate water in the iron(II) complex results in the higher temperature transition. In addition of that, the transition pattern has changed from the abrupt transition into the gradual transition types. Several studies of SCO properties of the complex Fe(II)-3-bpp reported that the transition type and the temperature transition were influenced by the type of counter anion and the amount of hydrate molecules. With various transition patterns and transition temperatures, the potential of Fe(II)-bpp complexes as SCO materials is more interesting to explored. Keywords: Iron(II) Complex, 3-bpp Ligand, Spin Crossover